Emergency surgical revascularization for catheter-induced dissection of the left main coronary artery - (:unkn) unknown (EKIN TIBBI YAYINCILIK LTD STI-EKIN MEDICAL PUBL, 2010)
Iatrogenic left main coronary artery dissection during selective coronary angiography is quite rare but a life-threatening complication. Since coronary blood flow to an extensive area of myocardium becomes compromised, prompt restoration of vessel patency to limit ischemia is extremely important. Although there are favorable results reported with both bail-out coronary stenting and emergent coronary artery bypass operation, the optimal management of patients with left main coronary artery dissection during invasive procedures remains uncertain. Here we present a 39-year-old woman with accidental dissection of iatrogenic left main coronary artery Successfully managed with emergent surgical revascularization.
Keywords: Dissection; emergent coronary artery bypass; iatrogenic; left main coronary artery; CARDIAC-CATHETERIZATION; DISEASE